Strategies of Islamic Religious Education Teachers (PAI) in Improving the Literacy and Writing of the Qur'an for Grade 4c Students of Elementary School Integrated Islamic Scholars Bau Bau Bau City - Nurhaliza, Sitti; Sulasri, Sulasri; Djalia, La Ode Sahrin (Journal of English Language and Education, 2026)
This research aims to systematically describe the instructional strategies implemented by Islamic Education (PAI) teachers to improve Qur’an reading and writing skills among fourth-grade students at SD Islam Terpadu Insan Cendekia, Baubau City. Qur’anic literacy is a fundamental competence in Islamic Education because the Qur’an serves as the primary source of Islamic teachings that encompass faith, morality, and character development; therefore, mastery of Qur’an reading and writing at the elementary level is essential to support students’ religious character formation and understanding of Islamic values in daily life. Preliminary observations at the research site indicated that some students had not yet achieved fluency in reading the Qur’an, as evidenced by inaccurate pronunciation of Arabic letters, limited understanding of tajwid rules, and low recitation fluency, highlighting the need for structured, systematic, and continuous instructional strategies. This study employed a qualitative approach with a descriptive analysis design, involving Islamic Education teachers and fourth-grade students as participants. Data were collected through classroom observations, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that PAI teachers implement a range of instructional strategies, including the application of Qur’an reading and writing (BTQ) methods, regular Qur’an reading habituation, gradual and repetitive practice, and the use of supportive learning media to create a positive learning environment and enhance student motivation. These strategies have a positive impact on students’ learning outcomes, as reflected in improved reading fluency, better understanding of tajwid rules, and increased interest in learning the Qur’an. Consequently, the study concludes that the instructional strategies applied by Islamic Education teachers play a crucial role in improving the quality of Qur’anic literacy learning at the elementary school level.